Legal Responsibility for Perpetrators of Burning Electronic Component Waste in Open Spaces - Tjahjanjani, Joejoen; Isnaini, Enik; Nida, Khairun; Pradana, Hendy Surya (Jurnal Independent, 2025)
Environmental pollution, especially caused by the open burning of waste electronic components, is very dangerous to the environment and living things. In addition, electronic waste has various forms, so there is a need for environmental legal regulations that regulate electronic waste specifically. The research method in this study uses a normative juridical research type, with a statute approach and a concept approach. The primary legal material used is Law Number 32 of 2009 concerning Environmental Protection and Management. From the results of the research carried out, it can be concluded that; First, that the legal basis for environmental pollution due to the open burning of electronic component waste refers to Government Regulation Number 101 of 2014 concerning the Management of Hazardous and Toxic Materials Article 5 Paragraph (2) because this type of waste should not be disposed of carelessly because the content in it can damage the environment. That for the management of electronic component waste, it must be carried out by a licensed and certified institution from the Ministry of Environment and Forestry Second, that legal sanctions against the perpetrators of the disclosure of electronic component waste include administrative sanctions that do not exempt the person in charge of the business and activity from the responsibility for recovery, civil sanctions are aimed at every person in charge of the business or activity that violates the law in the form of environmental pollution, criminal sanctions resulting from exceeding ambient air quality standards, water quality standards, seawater quality standards or deliberate environmental damage, because the effects of open burning due to electronic component waste are very harmful to the environment.